Analysis of the Implementation of Financial Management Patterns of Regional Public Service Agencies (PPK-BLUD) at Tanjungsari Health Center - Balishna, Mega; Andriani, Rian; Efawati, Yen (International Journal Administration, Business & Organization, 2025)
The implementation of the Regional Public Service Agency Financial Management Pattern 'Pola Pengelolaan Keuangan Badan Layanan Umum Daerah' (hereinafter referred to as PPK-BLUD) at the Puskesmas Tanjungsari demonstrates significant results in enhancing the quality of health services and financial management. This paper aims to analyze the implementation of PPK-BLUD based on Merilee Grindle's policy implementation theory; which highlights the relationship between policy content; and implementation context. The writing method used is a qualitative approach with data collection techniques including observation; interviews; and document reviews. The results of the study indicate that the autonomy provided through PPK-BLUD enables the Puskesmas Tanjungsari to manage its budget more flexibly; enhance financial transparency through the application of a digital economic system; and implement service innovations such as an electronic queuing system and QRIS payments. The success of the implementation is supported by oversight from the Health Office and community participation through discussion forums such as the Self-Awareness Survey (SMD) and Village Community Deliberation (MMD). However, challenges remain regarding employee commitment and coordination between teams that still need improvement. In conclusion, the implementation of PPK-BLUD at the Puskesmas Tanjungsari has succeeded in enhancing the efficiency of financial management; the quality of health services; and financial independence. This success can serve as a model for other Community Health Centers in implementing similar policies to improve health services in the region.